Independensi Auditor Sebagai Pemediasi Pengaruh Audit Fee dan Audit Tenure Pada Kualitas Audit - Premananda, Wayan Hari; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 24 No 2 (2018), 2018)
An auditor says capable of producing a qualified auditing report if the auditor is able to maintain its independence. The purpose of research to know and prove empirically the influence of audit fees and audit tenure on auditor independence. Prove empirically the effect of audit fees, audit tenure and auditor independence on audit quality. Audit fees and audit tenure on audit quality through auditor independence. The research was conducted at the Public Service Office of Bali Province. The number of samples of 44 auditors is determined by saturated sample technique. Data analysis technique used is path analysis (path analysis). Based on the results of the analysis. Audit ownership on auditor independence. Audit fees. Audit ownership on a positive audit. Auditor independence is high performing on audit quality. The higher the auditor's independence, the higher the audit quality will be generated.